Intermediate Accounting. - Spiller, Earl A.; Ross, Frank A. (The Accounting Review, 1973)
Reviews the book "Intermediate Accounting," 3rd ed., by Glenn A. Welsch, Charles T. Zlatkovich and John Arch White.